Suppressing asset price inflation: The confederate experience, 1861-1865 - Richard C.K. Burdekin; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 2000)
Confederate Treasury notes were convertible into government bonds at par. This provided an imbedded option value for the currency. Confederate interest-rate policy encouraged, and ultimately coerced, holders of Treasury notes to exchange these notes for bonds by imposing deadlines on their convertibility. In this paper we identify a long-run equilibrium relationship between the gold value of the bonds and the gold value of Confederate currency. We also show that the three funding acts aimed at precipitating the conversion of currency into bonds were effective in temporarily dampening inflationary pressures.
Keywords: N20; N40; 330; Confederacy; bonds; interest-rate pegging